2022
DOI: 10.1007/s00276-022-03008-4
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of palatal surface area with anthropometric dimensions of the head and face

Abstract: Purpose Saliva distribution over the palatal surface plays an important role in the perception of dry mouth. It is envisaged that non-invasive estimation of the palatal surface area by anthropometric measurements of the head and face can be useful in the assessment of oral dryness. For this purpose, the relationship between the palatal surface area and anthropometric measurements of the head and face was investigated. Methods The palatal surface was measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Furthermore, it has previously been reported that dental arches are poor predictors of transverse skeletal dimensions [ 25 ]. Conversely, Assy et al, 2022, reported that the palatal surface area was correlated with the facial width in a study comprising adults in the Netherlands [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has previously been reported that dental arches are poor predictors of transverse skeletal dimensions [ 25 ]. Conversely, Assy et al, 2022, reported that the palatal surface area was correlated with the facial width in a study comprising adults in the Netherlands [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The crossbite group comprised 22 females and 12 males, and the control group comprised 22 females and 12 males. Equal numbers of same-sex individuals were selected in the crossbite and control groups, and males and females were separately analyzed because of the sexual dimorphism of the facial parameters [ 19 , 20 , 21 ]. The median age in the crossbite group was 14.04 (interquartile range (IQR), 13.30–14.52) for females and 14.25 (IQR, 13.16–14.64) for males.…”
Section: Methodsmentioning
confidence: 99%